Globalization and Emerging Markets: With or Without Crash? - Martin, Philippe; Rey, Hélène (American Economic Review, 2006)
We analyze the effects of financial and trade globalization on the likelihood of financial crashes in emerging markets. While trade globalization always makes crashes less likely, financial globalization may make them more likely, especially when trade costs are high. Pessimistic expectations can be self-fulfilling and lead to a collapse in demand for goods and assets. Such a crash comes with a current account reversal and drops in income and investment. Lower-income countries are more prone to such demand-based financial crises. A quantitative evaluation shows our model is consistent with the main stylized facts of financial crashes in emerging markets.